2012
DOI: 10.1097/mao.0b013e31826bedbc
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hearing Loss and Saccular Dysfunction in Older Individuals

Abstract: Objective (1) Describe the association between hearing loss and dysfunction of each of the five vestibular end-organs – the horizontal, superior and posterior semicircular canals, saccule and utricle – in older individuals. (2) Evaluate whether hearing loss and vestibular end-organ deficits share any risk factors. Study design Cross-sectional study. Setting Academic medical center. Patients Fifty-one individuals age ≥70. Interventions Audiometry, head-thrust dynamic visual acuity (htDVA), sound-evoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 53 publications
2
62
2
1
Order By: Relevance
“…Nevertheless, because the compensatory mechanisms begins to fail during the process of aging, vestibular dysfunctions may be more common in the NIHL population than in the general population. This view is supported by clinical studies which have demonstrated a strong association between hearing loss and vestibular deficits in the elderly (Zuniga et al, 2012). Vestibular dysfunction, a risk factor for falling, may contribute to increased incidents of falls in the elderly with hearing loss (Viljanen et al, 2009; Lopez et al, 2011; Lin and Ferrucci, 2012).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, because the compensatory mechanisms begins to fail during the process of aging, vestibular dysfunctions may be more common in the NIHL population than in the general population. This view is supported by clinical studies which have demonstrated a strong association between hearing loss and vestibular deficits in the elderly (Zuniga et al, 2012). Vestibular dysfunction, a risk factor for falling, may contribute to increased incidents of falls in the elderly with hearing loss (Viljanen et al, 2009; Lopez et al, 2011; Lin and Ferrucci, 2012).…”
Section: Discussionmentioning
confidence: 78%
“…It has been reported that some individuals with noise-induced hearing loss (NIHL) also suffer from balance disorders (Oosterveld et al, 1982; Juntunen et al, 1987; Golz et al, 2001). Reduced vestibular caloric response (Manabe et al, 1995; Golz et al, 2001), reduced vestibular-evoked myogenic potentials (VEMP) (Wang et al, 2006; Wang & Young, 2007; Kumar et al, 2010; Akin et al, 2012; Zuniga et al, 2012), nystagmus (Man et al, 1980; Shupak et al, 1994; Oosterveld et al, 1982; Golz et al, 2001), and increased body sway (Ylikoski 1988; Kilburn et al, 1992) have been reported. Despite our understanding of the effect of noise on auditory function, the mechanisms underlying noise-induced vestibular deficiency remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found that HI increases the risk of falling, including a meta-analysis that found a 21% increased odds of falling among those with HI (Deandrea et al, 2010; Kulmala et al, 2009; Pluijm et al, 2006; Tromp, Smit, Deeg, Bouter, & Lips, 1998). There are multiple mechanisms by which HI could influence falls including shared pathological pathways (e.g., co-morbid vestibular dysfunction, cerebrovascular disease; Agrawal, Carey, Della Santina, Schubert, & Minor, 2009; Gates et al, 1993; Zuniga et al, 2012) or through decreased awareness of the auditory environment. Attentional resources are also essential for maintaining postural control and balance (Viljanen, Kaprio, Pyykko, Sorri, Pajala, et al, 2009; Woollacott & Shumway-Cook, 2002), and postural balance in older adults is markedly affected by the performance of concurrent cognitive tasks that utilize attentional resources.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in sensory epithelia are accompanied by a reduction in otoconia, mainly in the vertically positioned saccule (Johnsson & Hawkins, 1972). Besides a concurrent decay of saccular, utricular, cochlear and semicircular-canal function as part of the normal overall ageing process, there seems to be an additional association with lifetime noise exposure (Mc & Lawrence, 1958;Kumar et al, 2010;Zuniga et al, 2012).…”
Section: Introductionmentioning
confidence: 99%